Diabetic Muscle Infarction: An Uncommon Diabetic Complication With a Lack of Standardized Treatment. Issue 2 (21st February 2023) - Botero Suarez, Carlos S; Matos, Moises; Suryanarayanan, Sowmya
Abstract: Diabetic muscle infarction (DMI) is a rare yet serious complication that has been strongly associated with uncontrolled diabetes, although other risk factors are unclear. DMI is an uncommon complication of diabetes with a lack of structured guidelines for evaluation or management. End-stage renal disease (ESRD) could have further implications in patients with DMI in terms of management given that nonsteroidal anti-inflammatory drugs (NSAIDs), which have been shown to reduce the recovery times and recurrence of DMI, could be contraindicated. We present a rare case of DMI in an African American man with ESRD who presented for new-onset right lower-extremity pain and swelling. We discuss the challenges involved with the diagnosis and treatment of this rare condition. This case adds to the knowledge of DMI, which is limited because of the low incidence of this condition, and it helps us understand how this condition affects the African American population and patients with ESRD.